2022
DOI: 10.1002/anbr.202200005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Tissue Microenvironment Following Myocardial Infarction

Abstract: Significant progress has been made in methods for cardiac repair and regeneration within the past few decades; however, the diseased microenvironment of the infarct remains a limitation in the efficacy of therapies. A breadth of research is currently aiming to reverse this environment, focusing on immunomodulation, scavenging of oxidative species, and increasing oxygen levels within the tissue, either directly using materials or oxygen therapy or secondarily via angiogenesis and neovascularization techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 147 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…Research suggests that modulating the infarcted microenvironment toward a less diseased state may enhance the efficacy of these interventions. 5 It has been established that high doses of AA (reported as greater than 6 g per day, or 75 mg per kg per day), are safe in human populations. 64 Clinical trials have suggested infusing AA prior to reperfusion improves cardiac function, 22,23 however there are issues in traditional antioxidant therapy regarding obtaining therapeutic concentrations within the diseased tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research suggests that modulating the infarcted microenvironment toward a less diseased state may enhance the efficacy of these interventions. 5 It has been established that high doses of AA (reported as greater than 6 g per day, or 75 mg per kg per day), are safe in human populations. 64 Clinical trials have suggested infusing AA prior to reperfusion improves cardiac function, 22,23 however there are issues in traditional antioxidant therapy regarding obtaining therapeutic concentrations within the diseased tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Despite promising results in vivo, regenerative therapies for myocardial infarction have shown limited success in clinical trials. Research suggests that modulating the infarcted microenvironment toward a less diseased state may enhance the efficacy of these interventions 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue engineering is a rapidly expanding field which aims to design constructs which supplement or replace damaged biological tissue. The fabrication of a tissue-engineered graft can be undertaken in a variety of ways, including phase separation, bioprinting, gas foaming and electrospinning techniques [ 18 , 19 , 20 , 21 , 22 , 23 ]. From these methods, a dense interconnected network of material may be formed, which is termed a scaffold [ 24 ].…”
Section: Introductionmentioning
confidence: 99%